ANALISIS DAMPAK PENGEMBANGAN PARIWISATA ASIA FARM TERHADAP PEREKONOMIAN MASYARAKAT SEKITAR DIKECAMATAN TENAYAN RAYA - Sulistyowati, Ta Atika; Syahza, Almasdi; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: This study aims to analyze the impact of the development of Asian farm tourism on the economy of the surrounding community in the Tenayana Raya district. Communities in the area, it can still be said that the economy is middle to lower, with this tourism development is expected to be able to help the local economy. Asia Farm is one of the tours that carries out tourism development starting from the development of buildings and facilities, as well as renewing the tour. This type of research is a quantitative study, based on a total population of 86 people and a sample of 71 people using the simple random sampling technique. Data analysis used descriptive analysis with simple linear regression analysis. The purpose of this study is to describe the condition of tourism, and to identify the impact of tourism development on the economic conditions of the surrounding community. The results of this study indicate an increase in development starting from attractions, facilities, infrastructure, transportation, and hospitality after the development. However, there is a decline in the field of security, air pollution, conflicts between traders and the disruption of the existing environment. The percentage of people's income has increased from Rp. 2,000,000 - Rp. 3,000,000 / month, and business opportunities are 56.9% and job opportunities are also 56.9%. The positive impact of this development, starting in terms of income, business opportunities, and increased employment opportunities, while the negative impact in terms of safety, increased air pollution, and conflicts between traders and with this development it is also undeniable that the prices are the price of goods is very high from outside the tourism area.Key Words: Tourism development, community economy, positive and negative imacts